(untitled) (Research, Society and Development, 2021)
Among the Hydrographic Basins present in Brazil, the Amazon Hydrographic Basin stands out. To maintain the integrity of this basin, as well as the availability and quality of water, it is necessary to conserve the strips of native vegetation that border its water bodies, called riparian forests. In this region, urban occupation took place in the vicinity of water bodies, in an irregular and disordered manner. This situation increases the chance of flooding and landslides on the banks of rivers caused by the removal of riparian forests. Several municipalities that are located in the Amazon River Basin are in these conditions, for example, in the municipality of Rorainópolis-RR. Some stretches of Igarapé Chico Reis, the main water body that cuts through the city of Rorainópolis, are in a process of degradation, making restoration essential. Several restoration techniques can be applied in degraded riparian forests, as well as the use of indicators to assess restoration success. From the delimitation of the area, the possible techniques and indicators, the elaboration of a proposal for the intervention of degraded stretches in urban environments is indicated, in order to assist public policies in municipalities. In this sense, the general objective of this work was to carry out a theoretical framework on the restoration of riparian forests in the Amazon River Basin and to characterize the Igarapé Chico Reis located in the municipality of Rorainópolis-RR, as well as an intervention proposal for four stretches degraded areas of the Igarapé located within the municipality.